Plane stress state of media with plastic properties sensitive to the type of stress - Lomakin, Evgeny Victorovich; Melnikov, Andrey Mikhailovich (Computational Continuum Mechanics, 2009)
Plane stress problems are considered for the media whose plastic properties are sensitive to the type of stress. The properties of equations characterizing the distribution of stresses and velocities in plastic regions are studied. Some features of the solutions of the problems of the limit plastic equilibrium of media are considered. The problem of a plastic thin sheet with a linear cut subjected to tension far from the cut and normal to its plane is solved. The problem of tension of a strip with V-shape cuts is considered as well. The dependence of the limit load on the parameter characterizing the sensitivity of the plastic properties of media to the type of stress is studied.